Konflik Palestina Dengan Israel: (Nasib Pendidikan Anak-Anak Palestina) - Rian Rifki Eliandy; Amini Amini; Muhammad Heriadi; En Riskinta Tumanggor; Etti Aini Hasibuan (Journal Pendidikan Ilmu Pengetahuan Sosial, 2023)
This article was created with the title "Palestinian Conflict with Israel (The Fate of Palestinian Children's Education)" with the aim of informing readers about the conflict that occurred between Palestine and Israel, specifically which has an impact on the field of education. The method used in this article is descriptive qualitative with documentation techniques as the data collection technique. Thus it can be seen that the conflict between Palestine and Israel occurred because the Palestinian territories were seized by force in a cruel way by Israel. The United Nations has tried to provide regulations to resolve the conflict but to no avail because it received a veto right from the United States. Many bad impacts arising from the conflict, one of which is in the field of education. Indonesia has very good relations with Palestine, so that Indonesia provides a lot of aid for Palestine. This good relationship originated from Palestine's recognition of the independence of the Republic of Indonesia, so that good relations between Indonesia and Palestine are very closely intertwined like friends and brothers from the past until now.